Visualisation of Articular Cartilage Microstructure - Rowles, Christopher (Curtin University, 2016)
This thesis developed image processing techniques enabling the detection and segregation of biological three dimensional images into its component features based upon shape and relative size of the features detected. The work used articular cartilage images and separated fibrous components from the cells and background noise. Measurement of individual components and their recombination into a composite image are possible. Developed software was used to analyse the development of hyaline cartilage in developing sheep embryos.